Evaluation of antibacterial property and biocompatibility of Cu doped TiO2 coated implant prepared by micro-arc oxidation - kang, Binbin; Lan, Dongmei; Yao, Chao; Liu, Ping; Chen, Xiaohong; Qi, Shengcai (Frontiers in Bioengineering and Biotechnology, 2022)
In order to enhance osteogenic differentiation and antibacterial property of dental implants, volcano-shaped microporous TiO2 coatings doped with Cu were fabricated via micro-arc oxidation (MAO) on Ti. Cu-doped coating with different mass ratios of Cu were obtained by changing the concentration of copper acetate in the electrolyte. The structure of Cu-TiO2 coatings were systematically investigated. Element Copper was uniformly distributed throughout the coating. Compared with TiO2 coating, the Cu-doped can further improved proliferation of bone mesenchymal stem cells (BMSCs), facilitated osteogenic differentiation. The bacteriostasis experiments demonstrated that Cu-doped TiO2 coating possess excellent antibacterial property against Staphylococcus aureus (S. aureus) and Porphyromonas gingivalis (P. gingivalis).